Pengembangan media pembelajaran berbasis multimedia interaktif pada mata pelajaran Pendidikan Agama Kristen dan Budi Pekerti kelas 1 SD - Kristianawati Kristianawati; I Nyoman Sudana Degeng; Sugito Sugito (Jurnal Pendidikan Edutama, 2020)
Abstract: The number of Christian Religious Education (PAK) teachers in Indonesia is not proportional to the needs of schools, so that PAK teachers in public schools must double teach at 2 or 3 schools because of the small number of students and the number of PAK teachers. This condition requires the role of PAK teachers to be able to utilize technology properly, one of which is to use interactive multimedia-based learning media with Microsoft office PowerPoint in delivering PAK material. The purpose of this research development is to produce interactive multimedia-based learning media on PAK subjects and Character. The development model in this research is using the ADDIE development model with a theoretical design based on five steps namely Analysis, design, development, implementation, testing, dissemination. Testing is carried out using media experts, field practitioners (material experts) and group trials small one. The subjects of the small group trial were 12 PAK students of grade 1 at SDN Waru II Sidoarjo. By using the questionnaire sheets of media experts, field practitioners (material experts) and product evaluation questionnaire by small groups. The results of the field test product development (material / content expert) are 99%, the media expert test results are 93% and the small group trial results are 91%. From the three results obtained Very good, so interactive multimedia-based learning in PAK Mapel and grade 1 character is feasible to use. Keyword: interactive multimedia based learning media, Microsoft office power point, PAK Abstrak: Guru pendidikan Agama Kristen (PAK) di Indonesia jumlahnya tidak sebanding dengan kebutuhan sekolah, sehingga guru PAK di sekolah negeri harus merangkap mengajar 2 atau 3 sekolah karena minimnya jumlah murid dan jumlah guru PAK. Kondisi ini menuntut peran guru PAK untuk dapat memanfaatkan teknologi dengan baik salah satunya adalah dengan menggunakan media pembelajaran berbasis multimedia interaktif dengan Microsoft office power point dalam menyampaikan materi PAK. Tujuan penelitian pengembangan ini adalah menghasilkan media pembelajaran berbasis multimedia interaktif pada Mapel PAK dan Budi Pekerti. Model pengembangan dalam penelitian ini yaitu memakai model pengembangan ADDIE dengan desain teori yang dilakukan berdasar lima langkah yaitu Analisis, perancangan, pengembangan, implementasi, uji cob, penyebarluasan. Uji coba yang dilakukan menggunakan ahli media, praktisi lapangan (ahli meteri) dan uji coba kelompok kecil. Subjek uji coba kelompok kecil adalah 12 siswa PAK kelas 1 SDN Waru II Sidoarjo. Dengan menggunakan lembar angket ahli media, praktisi lapangan (ahli meteri) dan angket penilaian produk oleh kelompok kecil. Hasil pengembangan produk uji Paraktisi Lapangan (ahli materi/isi) 99%, hasil uji ahli media 93% dan hasil uji coba kelompok kecil 91%. Dari ketiganya didapatkan hasil Sangat baik, sehingga pembelajaran berbasis multimedia interaktif pada Mapel PAK dan budi pekerti kelas 1 SD layak digunakan. Kata kunci: media pembelajaran berbasis multimedia interaktif, Microsoft office power point, PAK